Around the extinctive prescription - Vidal Ramírez, Fernando (2020)
The course of time as a legal phenomenon and, more concretely, as a legal event, has special importance as it can extinguish a legal relationship either because it originates a new one, as in the case of usucapio or adverse possession; or it can also extinguish the claim deriving from the right inherent to it, as it is the case of negative prescription (lashes), or because it can extinguish the right itself, as it is the case of lapsing